Applicability of systematic screening for signs and symptoms of depression in family practice patients in Slovenia - Kozel, Dejan (Zdravniški vestnik, 2012)
Background: The prevalence of depression in primary care setting is high. About a half of patients with depression re ma in undetected. The aim of our study was to determine whether screening questionnaires assist family practitioners in identifying more patients with depression. Methods: The multicentric study included 25 medical teams (a family practitioner and a nurse) from several Slovenian regions and 2,328 patients (86 % of all patients who were asked to participate) above 18 years of age, who had not been treated for mental disorders and who during the study visited the ir family practitioners for different medical problems. The study was divided into two phases, which lasted three consecutive hours daily over a period of ten working days. In the first phase, the family practitioners recorded the number of new diagnoses of depression. Six weeks later, patients completed the Zung Self-Rating Depression Scale (ZSRDS) in the waiting room. At the same time, family practitioner used the Patient Health Questionnaire 9 (PHQ-9) to screen depression symptoms. Results: In the first phase, depression was diagnosed in 5.7 % participating patients, and in the second phase, 10.9 % of patients on ZSRDS or 9.6 % on PHQ-9 exceeded the cut-off score. The difference was statistically significant in ZSRDS (p < 001). Patients with positive screening results were mostly women - 16.9 % (PHQ-9) or 18.8 % (ZSRDS), and patients with chronic condition 22.0 % (PHQ-9) or 23.3 % (ZSRDS), both in age groups from 46 to 55 years. The family practitioners treated 94.6 % (PHQ-9) or 71.3 % (ZSRDS) of people with positive screening results. Conclusions: Results of both screening questionnaires were comparable. The screening tools can help family physicians in more efficient identification of depression. Targeted screening in high-risk groups, women and chronic patients in the age group from 46 to 55 years, would be reasonable.
Keywords: depresija (medicina); depression; diagnostika; družinska medicina; presejanje; primarna oskrba; primary care; screening